PSXV-21 Measuring reticulorumen pH and temperature in dairy cattle: How often is enough? Evaluation of different recording intervals from an automated reticulorumen bolus. (7th December 2018) - Mazon, G; Costa, J
Abstract: Battery life and pH measurement drifts are major limitations for long-term use of reticulorumen pH and temperature boluses. The objective of this study was to compare five different pH and temperature recording intervals to the standard 10 min recording interval on an automated reticulorumen bolus (iNVOTEC Animal Care, smaXtec, Graz, Austria). Sixteen lactating Holstein dairy cows producing 42.2 ± 10.3 kg of milk/d received a bolus on the first day of the eight-day trial. Cows were fed a balanced TMR ad libitum for three days and on the fourth day cows had their feed allowance reduced by half. On the fifth day cows received a grain mix to induce ruminal acidosis and were allowed to recover for 3 days. The 10-minute dataset was set as the gold-standard and used to generate datasets with five alternative recording intervals: 20, 30, 60, 120, and 240 min. Mean daily reticulorumen pH and temperature were generated for each recording interval. The relationship between the recording intervals of pH and temperature were analyzed using linear regressions and Bland-Altman plots. Data from the alternative recording interval was considered accurate if the slope and intercept from the regressions did not differ significantly from 1 and 0, respectively, and if mean bias from the Bland-Altman plots was within the 95% interval of agreement. For the pH regressions, estimates for the 20, 30, 60, and 120 min recording intervals met the accuracy criteria, whereas for the 240 min recording interval was not accurate (slope=0.96 ± 0.02; intercept=0.24 ± 0.12). For the temperature regressions, none of the alternative recording intervals met the criteria established. Mean daily pH and temperature biases from the Bland-Altman plots were acceptable for all recording intervals. In summary, pH recording intervals up to 120 min did not affect the quality of generated data. However, longer recording intervals seemed to affect temperature data.